(untitled) (Latakia University Journal -Medical Sciences Series, 2024)
Background: Benign prostatic hyperplasia (BPH) with LUTS represents the fourth most common disease in the male population over 50 years of age. When there is an obstruction at the level of the lower urinary tract accompanied by benign prostatic hyperplasia, surgical intervention is often the most applied option, despite the rate of accompanying complications that may occur. To ensure better results, appropriate indications for surgical intervention should be chosen, especially since BPH may not be the lesion causing the symptoms that the patient suffers from. Objective: To determine the diagnostic value of urinary flow study in selecting BPH patients who will undergo prostatectomy. Patients and methods: A randomized controlled clinical study, including all BPH patients attending the Department of Urology at Tishreen University Hospital in Lattakia and who will undergo surgery to remove enlarged prostate in the time period between 2022 - 2024. They were randomly divided into two groups: Group A (traditional investigations followed by surgical intervention to remove enlarged prostate), and group B (conventional investigations followed by urine flow studies). Results: The research sample included 55 patients, distributed into two groups: Group A (27 patients) and Group B (28 patients). The average age was 67.78 years, the average value for IPSS was 21.74, the average value for prostate volume was 45.85 cc, and the average value for urinary residual was 157.09. As for the results of the urine flow study for group B patients, the average value of the Maximum flow rate was 11.50 ml/second, detrusor pressure was 12.17 cm H2O, and bladder compliance was 22.25 ml/cm H2O. Based on these results, 20 patients from group B were referred for surgery, and the remaining patients were referred for neurological treatment. Conclusion: Urodynamic study contributes to determining the indication for surgical intervention in patients with BPH by accurately determining the cause of the urinary symptoms that the patient suffers from.